Servicio al cliente y su incidencia en la fidelización en la empresa Ferretera “Mi Ferretería” de la ciudad de Babahoyo, periodo 2024. - Zúñiga Santander, Carlos Eulogio (2025)
This study focuses on "Mi Ferretería", a hardware company located in the city of Babahoyo, analyzing how the quality of customer service affects the loyalty of its customers during the period 2024. It is hypothesized that deficiencies in customer service negatively influence consumer loyalty, which affects the growth and profitability of the company. The main objective is to evaluate the impact of customer service on the loyalty of "Mi Ferretería" customers, identifying areas for improvement and proposing strategies that strengthen the relationship with consumers. The mixed modality was chosen, that is, qualitative-quantitative, since the data will be collected directly at "Mi Ferretería" in Babahoyo, which allowed obtaining primary and relevant information. This modality ensures that the conclusions are based on real and contextualized data, facilitating direct interaction with customers to obtain genuine perspectives on their experience with customer service. The results showed that there is a significant association between customer service quality and customer loyalty at "Mi Ferretería", according to the results of the Chi-Square test. The Spearman coefficient (0.78) indicates a strong positive relationship between service perception and loyalty, confirming that satisfied customers are more likely to make a repeat purchase.